2017
DOI: 10.18410/jebmh/2017/99
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Airway and Predicting Difficult Endotracheal Intubation in Diabetic Patients- A Comparison With Nondiabetic Patients

Abstract: BACKGROUND The aim of this study is to evaluate the various clinical parameters of airway assessment and their ability to predict difficult laryngoscopy and intubation in diabetic patients as compared to nondiabetic patients. MATERIALS AND METHODS Out of 120 patients, 60 diabetics (group-D) and 60 nondiabetics (group-N) were studied preoperatively for various airway indices such as the modified Mallampati Test (MPC), Thyromental Distance (TMD), Degree of Head Extension (HE), the Palm Print Index (PP) and the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, Gondane et al and Thomas and Hashim reported slightly lower specificities of 41.18% and 68.1% by Mallampati grading in the sitting position, respectively ( 9 , 10 ). Baig and Khan reported a specificity of 99.2% among the diabetic population, which was comparable to our finding ( 14 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, Gondane et al and Thomas and Hashim reported slightly lower specificities of 41.18% and 68.1% by Mallampati grading in the sitting position, respectively ( 9 , 10 ). Baig and Khan reported a specificity of 99.2% among the diabetic population, which was comparable to our finding ( 14 ).…”
Section: Discussionmentioning
confidence: 92%
“…Gonadane et al conducted a study among the diabetic population and found that Mallampati grading in the sitting position detected 21 out of 26 difficult cases with a sensitivity of 80.77% ( 9 ). In contrast, Thomas and Hashim reported that Mallampati grading could not predict difficult intubation and suggested that Palm Print was a better predictor ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The big three diabetes signs are polyuria and polydipsia (due to the osmotic effects of glucose, hyperglycemia causes elimination of glucose with water from the kidney, causing feeling of thirst), the 3 rd sign is Polyphagia due inability of the cells to take up glucose 14 .…”
Section: Symptomsmentioning
confidence: 99%
“…Results of chronic hyperglycemia are: Microvascular (retinopathy, neuropathy and nephropathy), macro vascular (hypertension and hyperlipidemia which lead to CHD) and immune dysfunction 14 . Overall, DM led to reducing phagocytosis, chemotaxis and the bactericidal capacity of the inflammatory response and therefore, hyperglycemic burn patients have a high risk for infections 15 .…”
Section: Consequences Of Hyperglycemiamentioning
confidence: 99%